1997
DOI: 10.1063/1.365992
|View full text |Cite
|
Sign up to set email alerts
|

Angular and energy dependence of ion bombardment of Mo/Si multilayers

Abstract: The process of ion bombardment is investigated for the fabrication of Mo/Si multilayer x-ray mirrors using e-beam evaporation. The ion treatment is applied immediately after deposition of each of the Si layers to smoothen the layers by removing an additional thickness of the Si layer. In this study the parameters of Kr ϩ ion bombardment have been optimized within the energy range 300 eV-2 keV and an angular range between 20°and 50°. The optical performance of the Mo/Si multilayers is determined by absolute mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…From previous experiments, where ion bombardment has been investigated, it has been concluded that during ion bombardment the smoothening effect is mainly caused by viscous flow. 35 Whether the smoothing effect by temperature optimization is caused by diffusion or viscous flow needs to be investigated in the future.…”
Section: Modelmentioning
confidence: 99%
“…From previous experiments, where ion bombardment has been investigated, it has been concluded that during ion bombardment the smoothening effect is mainly caused by viscous flow. 35 Whether the smoothing effect by temperature optimization is caused by diffusion or viscous flow needs to be investigated in the future.…”
Section: Modelmentioning
confidence: 99%
“…The MoN/SiN multilayer coatings used in this work have been deposited on superpolished Si substrates using e-beam evaporation of Mo atoms and magnetron sputtering of Si atoms in a UHV background of 1×10 8 mbar, with post-deposition smoothing using low energy ion treatment of the Si layers [15][16][17][18]. Nitridation of the Mo and Si layers was achieved by low energy nitrogen ion treatment during deposition [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…Concerning ion beam process, energetic ion bombardment increases viscous flow and surface diffusion of adatom, which can significantly reduce interface roughness of Ta/ V/Ta films prepared by IBAD. 10 It has been also reported that multilayer films produced with e-beam deposition in combination with ion bombardment showed a reduced interface roughness. 11,12 The additional sharp interfaces between Ta and V can modify the microstructure of Ta film, in particular, the structure of grain boundaries.…”
Section: Resultsmentioning
confidence: 95%